ARTI DAN TUJUAN PENDIDIKAN SEUMUR HIDUP SERTA DASAR-DASAR PEMIKIRAN DAN IMPLIKASI KONSEPNYA - Nata Hudin, Mukhlisin; Sabariani, Ranti; Safitri, Sani; Bachtiar Pamulaan, Alif (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
Lifelong education is an ongoing learning process from birth to the end of life. The concept is rooted in the human need to continuously develop and adapt in the face of social, technological and economic challenges. Education is not limited to formal channels in schools, but also includes informal and non-formal education that occurs in families and communities. The Indonesian government has recognized the importance of lifelong education in various regulations, including the MPR Decree and the National Education System Law, to improve the quality of human resources as a whole and sustainably. This research uses a descriptive qualitative method in the form of a literature study approach that refers to 10 literature sources. The results show that lifelong education plays a key role in shaping individuals and communities that are resilient and responsive to change. The implications of this concept include functional literacy, vocational, professional, civic education, as well as education that supports social development. In conclusion, lifelong education not only provides learning opportunities for individuals of all ages but also contributes to sustainable national development.